2017
DOI: 10.1088/1748-9326/aa893b
|View full text |Cite
|
Sign up to set email alerts
|

Impact of biofuels on contrail warming

Abstract: Contrails and contrail-cirrus may be the largest source of radiative forcing (RF) attributable to aviation. Biomass-derived alternative jet fuels are a potentially major way to mitigate the climate impacts of aviation by reducing lifecycle CO 2 emissions. Given the up to 90% reduction in soot emissions from paraffinic biofuels, the potential for a significant impact on contrail RF due to the reduction in contrail-forming ice nuclei (IN) remains an open question. We simulate contrail formation and evolution to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 40 publications
1
49
0
Order By: Relevance
“…Target year The net radiative forcing impacts of contrails have been quantified using both global climate models (Chen and Gettelman, 2013;Ponater et al, 2002) and dedicated modeling approaches such as the Contrail Cirrus Prediction Tool (CoCiP) (Schumann, 2012) and the Contrail Evolution and Radiation Model (CERM) (Caiazzo et al, 2017). These approaches have resulted in estimates of total contrail radiative forcing ranging from +15.2 mW/m 2 (Chen and Gettelman, 2013) to +63.0 mW/m 2 (Schumann et al, 2015) for 2006, as shown in Table 1.…”
Section: Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…Target year The net radiative forcing impacts of contrails have been quantified using both global climate models (Chen and Gettelman, 2013;Ponater et al, 2002) and dedicated modeling approaches such as the Contrail Cirrus Prediction Tool (CoCiP) (Schumann, 2012) and the Contrail Evolution and Radiation Model (CERM) (Caiazzo et al, 2017). These approaches have resulted in estimates of total contrail radiative forcing ranging from +15.2 mW/m 2 (Chen and Gettelman, 2013) to +63.0 mW/m 2 (Schumann et al, 2015) for 2006, as shown in Table 1.…”
Section: Sourcementioning
confidence: 99%
“…According to recent market forecasts, global air traffic is projected to grow by ~4.5% per year over the next 20 years (Airbus 2018, Boeing 2019). The scaling of contrails radiative forcing impacts with the expected traffic growth will depend on multiple aspects, especially (i) potential changes in contrail formation likelihood with changes in engine efficiency and the use of biofuels (Schumann, 2000;Caiazzo et al, 2017); (ii) the emergence of new markets with different prevailing atmospheric conditions (Boeing, 2019); and (iii) increased likelihood of contrail-contrail overlap as existing markets and flight paths become more saturated.…”
Section: Sourcementioning
confidence: 99%
“…Similarly, we do not consider the reduction of non-CO 2 climate pollutants emitted by the aviation sector in the mitigation scenarios. However, offsetting schemes such as CORSIA do implement the use of biofuels as well as aircraft technology and air traffic management improvements, both of which have the potential to impact future emissions of non-CO 2 climate pollutants and the density of contrail-cirrus (Bock and Burkhardt, 2019;Caiazzo et al, 2017;Burkhardt et al, 2018). While the influence of these changes on the non-CO 2 impact of international aviation is currently not well estimated, their impact should be considered in future analyses as understanding develops.…”
Section: Avoided Warming From Mitigation Measuresmentioning
confidence: 99%
“…However, these rates will be outpaced by the anticipated global aviation demand growth of around 4.5% per year [10,11]. In contrast to fuel efficiency improvements, low-carbon fuels (e.g., biofuels) could partially decouple CO 2 emissions from aviation growth, although these options face cost and scale limitations and do not significantly help with non-CO 2 impacts [12,13], except for a potential thinning of contrails with an uncertain sign of the effect [14,15]. Similarly, liquid hydrogen [16] and liquified natural gas [17] could greatly reduce direct CO 2 emissions, but these fuels' higher hydrogen content would result in enhanced contrail and cirrus cloud formation.…”
Section: Introductionmentioning
confidence: 99%